The characteristics of coordination process in construction projects - Alaloul, W.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
Modern construction projects are no longer confined to a single discipline but are generally multidisciplinary. An independency relationship between a large number of stakeholders required to be managed in construction projects procurement and execution that need continuous coordination. Coordination function is to harmonize the different activities, so that the determined objectives can be reached effectively. However, the study of coordination characteristics are the way to assess the status of coordination in construction projects. Through the literatures, the most important characteristics of coordination process were identified. Quantitative approach was used to investigate them through questionnaire. The data were analyzed by means of statistical analysis and Chi-square test. The analysis showed that, 45.5 of the respondents mentioned to a moderate level of knowledge about coordination, however 44.6 were commonly applied coordination culture. Nevertheless, about 60 believed that, ability and willingness are the main obstacle of coordination application. At the same time, 75 considered coordination effect as significantly improve the project performance. In the future, 70 of the respondents will always apply coordination consideration from their personal motivation. The results of Chi-square show a significant dependent relationship between the position and organization function variables and the eight coordination characteristics. Â© 2015 IEEE.